EPCO-13. IDENTIFYING REGULATORS OF GLIOMA CELL STATE DIVERSITY AND EVOLUTION VIA JOINT SINGLE NUCLEUS RNA AND CHROMATIN ACCESSIBILITY. (14th November 2022) - Johnson, Kevin; Anderson, Kevin; Nehar-Belaid, Djamel; Varn, Frederick; Gujar, Amit; Courtois, Elise; Robson, Paul; Moon, Hyo-Eun; Golebiewska, Anna; Paek, Sun Ha; Niclou, Simone; Verhaak, Roel
Abstract: Glioma cellular heterogeneity and plasticity represent fundamental obstacles to effective therapies. Understanding the determinants that govern glioma cell diversity and adaptability is critical to overcoming treatment resistance. Recent single cell DNA methylation studies have demonstrated that dynamic epigenetic alterations facilitate glioma cell state shifts and stress response. However, information regarding other modes of epigenetic gene regulation, such as chromatin accessibility, and how therapy shapes cellular heterogeneity remains limited. To determine the critical regulators of glioma cell state plasticity under treatment, we profiled 36 tumors (n = 23 adult patients) with joint single nucleus RNA and ATACseq including 13 longitudinal initial – recurrent pairs that yielded a total of 79, 945 cells (37, 883 malignant cells). We identified chromatin peaks that were uniquely open in glioma cells (n = 14, 462 peaks, FDR < 0.05) compared with tumor microenvironmental cells including neuronal, perivascular, glial, and immune populations. Among malignant cells, differentiated-like cells exhibited more recurrent regions of accessibility than stem-like cells. These populations could be further delineated by differential peak enrichment of transcription factor binding sites in the stem-like (TCF12, ASCL1), differentiated-like (SMARCC1, JUN), and proliferating stem-like (E2F4) malignant cells nominating these transcription factors as master regulators. We confirmed that these cell state-specific open chromatin peaks overlapped enhancer regions via single nucleus multiomics and bulk H3K27ac profiling in 3 patient-derived cell lines. We further demonstrated that there are cell state-specific chromatin changes at recurrence with a trend toward a more open chromatin state that was associated with coordinated transcriptional changes. Finally, we incorporated matched longitudinal whole genome sequencing data to evaluate mutational profiles and differentiate between predominantly epigenetically driven changes and epigenomic co-evolution with the genome. Together, these findings define the key epigenetic switches that shape glioma cell states and facilitate plasticity during tumor progression.